14-3-3ε protein-loaded 3D hydrogels favor osteogenesis - Aldana, Ana A.; Uhart, Marina; Abraham, Gustavo A.; Bustos, Diego M.; Boccaccini, Aldo R. (Journal of Materials Science: Materials in Medicine, 2020)
3D printing has emerged as vanguard technique of biofabrication to assemble cells, biomaterials and biomolecules in a spatially controlled manner to reproduce native tissues. In this work, gelatin methacrylate (GelMA)/alginate hydrogel scaffolds were obtained by 3D printing and 14-3-3ε protein was encapsulated in the hydrogel to induce osteogenic differentiation of human adipose-derived mesenchymal stem cells (hASC). GelMA/alginate-based grid-like structures were printed and remained stable upon photo-crosslinking. The viscosity of alginate allowed to control the pore size and strand width. A higher viscosity of hydrogel ink enhanced the printing accuracy. Protein-loaded GelMA/alginate-based hydrogel showed a clear induction of the osteogenic differentiation of hASC cells. The results are relevant for future developments of GelMA/alginate for bone tissue engineering given the positive effect of 14-3-3ε protein on both cell adhesion and proliferation.
CRIS-Team Scopus Importer:2020-11-13